KARAKTERISTIK LAHAN DAN KOMPOSISI JENIS TANAMAN PENYUSUN AGROFORESTRY DI KECAMATAN SESEAN KABUPATEN TORAJA UTARA - Budirman Bachtiar; Ratu M Sandabunga (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2022)
Agroforestry system recently developed by the community to meet their needs. But many people’s don’t understand yet to select suitability plants on the agroforestry land. This study aims to determine the land characteristics and components of agroforestry in District Sesean, Toraja District. This research caried out in the way comparethe requireiment of plants and charactristic at land. Plants in research location are robusta coffee, cocoa, banana, mangosteen, buangin (pine mountain), aren, bamboo betung, and uru. The result of research indicated land suitability of plants are moderately suitable (S2) to marginal suitable (S3). Limitation factors that limit plant growth is predominantly rainfall and also temperature, but both of these limiting factors are difficult and can not be repaired. Keywords :Agroforestry, Land characteristics, Plants